D-galactose protects the intestine from ionizing radiation-induced injury by altering the gut microbiome - Zhu, Tong; Wang, Zhouxuan; He, Junbo; Zhang, Xueying; Zhu, Changchun; Zhang, Shuqin; Li, Yuan; Fan, Saijun (Journal of radiation research, 2022)
This article aims to investigate the protection of the intestine from ionizing radiation-induced injury by using D-galactose (D-gal) to alter the gut microbiome. In addition, this observation opens up further lines of research to further increase therapeutic potentials. Male C57BL/6 mice were exposed to 7.5 Gy of total body irradiation (TBI) or 13 Gy of total abdominal irradiation (TAI) in this study. After adjustment, D-gal was intraperitoneally injected into mice at a dose of 750 mg/kg/day. Survival rates, body weights, histological experiments and the level of the inflammatory factor IL-1β were observed after TBI to investigate radiation injury in mice. Feces were collected from mice for 16S high-throughput sequencing after TAI. Furthermore, fecal microorganism transplantation (FMT) was performed to confirm the effect of D-gal on radiation injury recovery. Intraperitoneally administered D-gal significantly increased the survival of irradiated mice by altering the gut microbiota structure. Furthermore, the fecal microbiota transplanted from D-gal-treated mice protected against radiation injury and improved the survival rate of recipient mice. Taken together, D-gal accelerates gut recovery following radiation injury by promoting the growth of specific microorganisms, especially those in the class Erysipelotrichia. The study discovered that D-gal-induced changes in the microbiota protect against radiation-induced intestinal injury. Erysipelotrichia and its metabolites are a promising therapeutic option for post-radiation intestinal regeneration.